Optimasi Parameter Campuran Material Paving Block Ramah Lingkungan Untuk Memaksimalkan Kuat Tekan dengan Metode Taguchi - Rohmat, Rohmat; Sugiono, Didik; Hidayat, Hidayat (Politeknik ATI Padang, 2025)
The increasing amount of industrial and domestic waste poses a serious challenge to environmental sustainability. Utilizing waste materials as substitutes in construction offers a promising solution. This study aims to optimize the composition of eco-friendly paving blocks by incorporating seashell waste and coconut coir powder using the Taguchi method. Four factors including cement, sand, seashell powder, and coconut coir powder were analyzed at four variation levels based on an orthogonal array L16 (4⁴), producing 16 experimental combinations. Compressive strength was used as the main performance parameter. The Signal-to-Noise (S/N) ratio analysis showed that coconut coir powder had the greatest effect on compressive strength, followed by seashell powder, cement, and sand. The optimal composition was obtained with 643.23 g of cement, 2289.60 g of sand, 228.961 g of seashell powder, and no coconut coir powder. Although ANOVA results indicated no statistically significant factors (p > 0.05), coconut coir powder had the strongest influence. The regression model explained 56.25% of the variation in compressive strength. These findings suggest that seashell waste can serve as a viable partial replacement material for producing environmentally friendly and cost-effective paving blocks.